2008
DOI: 10.1182/blood-2008-05-154278
|View full text |Cite
|
Sign up to set email alerts
|

Graft rejection as a Th1-type process amenable to regulation by donor Th2-type cells through an interleukin-4/STAT6 pathway

Abstract: Graft rejection has been defined as the mirror image of graft-versus-host disease, which is biologically characterized primarily as a Th1-type process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Another fundamental role of JAK-STAT signaling is to dictate immune cells activation and differentiation (13). We have previously shown that STAT signaling is not dispensable for development of T-cell alloreactivity (14) in graft rejection experiments and that STAT3 activation is of fundamental importance for the onset of acute GVHD (15). In addition, other reports have extensively studied the role of different proteins of the STATs family for the onset of GVHD (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Another fundamental role of JAK-STAT signaling is to dictate immune cells activation and differentiation (13). We have previously shown that STAT signaling is not dispensable for development of T-cell alloreactivity (14) in graft rejection experiments and that STAT3 activation is of fundamental importance for the onset of acute GVHD (15). In addition, other reports have extensively studied the role of different proteins of the STATs family for the onset of GVHD (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, delayed administration of rapamycin-resistant Th2 cells after an initial donor Th1-type response optimized the balance of GVT effects and GVHD, 16 thereby indicating that a mixed pattern of Th2 and Th1 immune reconstitution was desirable in the setting of cancer therapy. And finally, rapamycinresistant Th2 cells prevented graft rejection through host T-cell conversion to a Th2-type profile, 19 thus illustrating that this novel donor T-cell population may have particular application in transplant settings associated with increased graft rejection, such as the use of low-intensity host conditioning.…”
mentioning
confidence: 97%
“…In our studies, we found that ex vivo rapamycin increased the capacity of interleukin (IL) 4 polarized donor Th2 cells to promote a balanced pattern of Th2/Th1 immune reconstitution for promotion of GVT effects and alloengraftment with reduced GVHD. [16][17][18][19] Ex vivo rapamycin creates a state of T-cell starvation that induces autophagy, 20 thereby resulting in an antiapoptotic T-cell phenotype that dictates persistent T-cell engraftment in mouse-into-mouse 18 or human-into-mouse 21 transplantation models. Rapamycin-resistant Th2 cells inhibited GVHD by multiple mechanisms, including IL-4 and IL-10 secretion, consumption of IL-2 required for propagation of pathogenic effector T cells, and modulation of host antigen-presenting cell.…”
mentioning
confidence: 99%
“…The increasingly expressed genes include FYVE domain NF-κB activation (39). Stat1 (10:1, p = 0.003) deficient T cells cannot differentiate into Th1-type cells in vivo containing 1 (Ankfy1), basic helix-loop-helix domain containing, class B, 2 (Bhlhb2), Glrx2, interferon regulaand fail to mediate rejection (41). Constitutive overexpression of Stat1 leads to the suppression of the cytotory factor 2 (Irf2), mediator of RNA polymerase II transcription, subunit 8 homolog (yeast) (Med8), mediator toxic response and renders the cells resistant to ionizing radiation (IR) and other inducers of cell death (30).…”
Section: Cd25mentioning
confidence: 99%